Influence of housing system on egg weight and shell physical quality indicators of laying hens eggs - Henrieta Arpášová (Scientific Papers Animal Science and Biotechnologies, 2021)
In this experiment the effects of different housing systems on physical indicators of egg yolk and egg albumen quality of table eggs were studied. Hens of laying hybrid Lohmann Brown Lite were housed in two different housing systems, in enriched cage or on floor housing system. In both systems, the hens were kept under standard bioclimatic conditions. Eggs (n = 1080) were collected from the first phase of the laying cycle, at monthly intervals, at the age of laying hens 30-42 weeks. Egg weight (g), egg specific weight (g.cm-3), egg shape index (%), eggshell weight (g), eggshell percentage (%), and average eggshell thickness (µm) were evaluated. In the indicators of the whole egg quality was statistically significantly higher (P<0.001) the average weight of eggs produced by laying hens kept in enriched cage (66.3 ± 3.6) mean ± SD in comparison with the eggs from laying hens housed on litter (64.3 ± 4.0) mean ± SD. Similarly, in eggshell quality indicators (weight, proportion, average thickness) there were significantly higher differences in favor of the eggs from caged breeding. The values of the average egg shell thickness (µm) in the order of groups (392 ± 24.6; 377 ± 24.3) (mean ± SD). The results obtained show that the eggs from caged breeding achieved better results in more quality indicators compared to the eggs from litter breeding.